2012
DOI: 10.1021/cs300140j
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Layer Functionalized Poly(Ionic Liquid) Coated Magnetic Nanoparticles: Highly Recoverable and Magnetically Separable Brønsted Acid Catalyst

Abstract: A functionalized poly(ionic liquid) coated magnetic nanoparticle (Fe 3 O 4 @PIL) catalyst was successfully synthesized by polymerization of functionalized vinylimidazolium in the presence of surface modified magnetic nanoparticles. The resulting heterogeneous catalyst is shown to be an efficient acidic catalyst for synthesis of 1,1-diacetyl from aldehydes under solvent free conditions and room temperature in high yields. Also, the catalyst shows good activity for the deprotection reaction of acylals. After com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 45 publications
1
82
0
Order By: Relevance
“…Then the surfaces of magnetic particles were modified by an addition of 3.0 g sodium oleate. After 8 h, the sediment was collected using an external magnet, washed in anhydrous ethanol and deionized water, and calcined after being dried to obtain the Fe3O4 magnetic powder (Xuan et al 2009;Lai et al 2011a;Pourjavadi et al 2012;Liang 2015). …”
Section: Preparation Of Fe3o4 Particlesmentioning
confidence: 99%
“…Then the surfaces of magnetic particles were modified by an addition of 3.0 g sodium oleate. After 8 h, the sediment was collected using an external magnet, washed in anhydrous ethanol and deionized water, and calcined after being dried to obtain the Fe3O4 magnetic powder (Xuan et al 2009;Lai et al 2011a;Pourjavadi et al 2012;Liang 2015). …”
Section: Preparation Of Fe3o4 Particlesmentioning
confidence: 99%
“…Recently, different types of catalyst support materials such as polymer supports [4][5][6][7][8][9][10], ionic liquid supports [10][11][12], inorganic supports [13][14][15][16][17][18], metal organic frame supports [19], and nanocomposite supports [20][21][22] have been invented for immobilizing catalysts on beads, surfaces, and membranes, and so forth [23]. Of these, magnetic iron oxide nanocomposites have been the most widely used support material [2] because they offer enormous surface area with more binding sites; this reduces the disadvantages of heterogeneous catalysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some novel magnetic solid acid catalysts have been developed. Their magnetic property can play a key role to economically recover the catalysts from reaction mixtures (Gill et al, 2007;Kara and Erdem, 2011;Pourjavadi et al, 2012;Tan et al, 2012;Zillillah et al, 2012). For instance, Pourjavadi et al (2012) reported the synthesis of heterogeneous acid catalyst in which ferrimagnetic, Fe 3 O 4 , nanoparticles were coated with multiple layers of polyimidazolium functionalized with sulfonic acid by an ionexchange method.…”
Section: Introductionmentioning
confidence: 99%
“…Their magnetic property can play a key role to economically recover the catalysts from reaction mixtures (Gill et al, 2007;Kara and Erdem, 2011;Pourjavadi et al, 2012;Tan et al, 2012;Zillillah et al, 2012). For instance, Pourjavadi et al (2012) reported the synthesis of heterogeneous acid catalyst in which ferrimagnetic, Fe 3 O 4 , nanoparticles were coated with multiple layers of polyimidazolium functionalized with sulfonic acid by an ionexchange method. In another example, micro-beads were coated with poly(divinylbenzene-4-vinylpyridine) mixed with Fe 3 O 4 nanoparticles by copolymerization to synthesize a solid acid catalyst, of which the surface was functionalized with sulfonic acid by free radical polymerization technique (Kara and Erdem, 2011).…”
Section: Introductionmentioning
confidence: 99%